"IMPROVING STUDENTS WRITING ABILITY THROUGH COMPLETION SHORT STORY OF SECOND YEAR HIGH SCHOOL AT UNAI LABSCHOOL" - Panjaitan, Nelson B.; Silitonga, Okamura; Silitonga, Mian (Journal of Language Pedagogy, 2011)
This research is entitled "Improving Students Writing Ability Through Completion Short Story Of Second Year Junior High School at Unai Labschool". This research was administered to answer the question "does completion short story significantly improve writing capability of second year junior high School at Unai Lab School?" The data were collected through pre-test and postÂ test, administered to 15 students and the data was analyzed by using T-test. The researcher gave the pre-test and post-test through incomplete short story form to collect the data. And the data is analyzed by using T-Test in SPSS (Statistical for service Solution) The results showed that the participants of writing achievement was improved through Completion Short Story Strategy and the score gained by participants showed that there was a significant effect of Completion Short Story Strategy. It is strong enough to improve the students writing ability. The achievements showed that the mean difference between pre-test and post-test is 18 the t wâaed= -4.306 < t pie= -2.048 with significance level in 0.05. Standard error mean of pre-test is 3.73078 and post-test 2.02477. The researcher hopes that the finding of present study could give some contribution to the improvement on the teaching writing especially for junior high school at Unai.